Apprehension and interest: Therapist and student views of the role emerging placement model in the Republic of Ireland. Issue 1 (3rd April 2017) - Linnane, Esther; Warren, Alison
Abstract : Purpose: Role-emerging placements have been used internationally within occupational therapy education but are relatively new to Ireland. At times, there has been a debate in the profession regarding the use of this placement model. This paper aims to generate views from both occupational therapists and occupational therapy students on the use of role-emerging placements in the Republic of Ireland. Design/methodology/approach: Electronic surveys were administered to occupational therapy students and occupational therapists in Ireland. Quantitative data were analysed using the SPSS Statistics software package and the content of the open question responses were analysed into themes. Findings: Occupational therapists (n = 60) and occupational therapy students (n = 45) indicated that there were inconsistent views surrounding role-emerging placements. It is deemed as an effective method for student learning, but apprehension exists around inclusion within occupational therapy programmes in the Republic of Ireland. Preference was indicated towards inclusion of role-emerging placements on a part-time basis within formal occupational therapy education. Originality/value: Both respondent groups viewed that role-emerging placements can positively influence new areas of occupational therapy practice and concern over the use of the placement model requires further exploration and debate. This study is from an Irish context, although there are similarities with other countries' use of the placement model. There is a need for research through an in-depth exploration of the learning experience of undertaking role-emerging placements from the students' perspective and identification of supports required to promote an optimal learning experience.